Academic Silence And Its Relationship To Emotional Regulation According To Gender Among Students Of The Faculty Of Physical Education And Sports Sciences - Salman, Dr. Suhair Rahman; Amana, Hiba Karim (Adolescência e Saúde, 2026)
The study aims to build and design two scales for academic silence and emotional regulation among students of the College of Physical Education and Sports Sciences, University of Dhi Qar, to identify the relationship between the two scales for academic silence and emotional regulation among students of the College of Physical Education and Sports Sciences, University of Dhi Qar, to identify the differences in the gender variable between (male and female students) in the two scales for academic silence and emotional regulation among students of the College of Physical Education and Sports Sciences, University of Dhi Qar. The research population consisted of (852) male and female students, divided into a pilot sample of (12) male and female students, a construction sample of (120) male and female students, and an application sample of (80) male and female students, as the percentage of the research sample was (26.29%)., The researcher reached several conclusions, the most important of which was the emergence of high, very high, medium and weak levels in different proportions, but the medium level is the most prevalent in the academic silence scale among students of the College of Physical Education and Sports Sciences/University of Dhi Qar. A significant correlational relationship emerged between academic silence and emotional regulation among students of the College of Physical Education and Sports Sciences/University of Dhi Qar. The process of regulating emotions among university students depends on their level of academic silence.